Determination of the geometric properties of rolled profiles and built-up bar sections used in ship hull structures when assessing their elestic bending, shear, torsion, and plastic bending strength - 362016 Ivanov, Lyuben D.; Liu, Shewen (Houston, TX : American Bureau of Shipping, 2000)
19